Tunable high frequency seawater antenna - Ling, Sze Ling (2016)
This research is on the study and design of a tunable high frequency (HF) seawater antenna for military applications. HF is for the range of radio frequencies between 3 MHz to 30 MHz. This corresponds to a wavelength of 100 m to 10 m. Since the physical size of an antenna is determined by its wavelength, approximately half a wavelength, λ/2, the size of the HF antenna is large and requires significant amount of space for installation and implementation. In a small island such as Singapore where land space is limited, operation of HF communications becomes a challenge. The objective of this research is to design and implement a tunable HF antenna that requires minimum amount of land space. It is well known that the electrical conductivity of seawater is around 4 S/m. The idea is to make use of seawater to design an antenna such that the antenna can be “switched on” or “off” at will. By varying the length of the water stream, the frequency of the antenna can be varied. Along the coast or at sea, the implementation of the tunable seawater antenna is simple and practical. On land, such antennas can be implemented in reservoirs or as water features by altering the electrical properties of the water. Simulation results for the monopole antenna was presented at the HF band. The characteristics of the ferrite coil are being examined and analyzed. By varying the outer radius, core radius and the permeability of the ferrite coil, the performance of the antenna will also be varied. Different stream lengths will cause different resonant frequencies response of the seawater monopole antenna. The proposed seawater monopole antenna meets the benefit of tunability. The performance of the seawater monopole antenna improves when the radius of the water stream increases. The seawater bend monopole antenna has a lower resonant frequency due to the additional length of the bend. The seawater monopole antenna including the falling water droplets that was observed in the experiment does not has any effect on the performance of the seawater antenna.